Mental Contrasting of a Negative Future with a Positive Reality Regulates State Anxiety - Brodersen, Gunnar; Oettingen, Gabriele (Frontiers in Psychology, 2017)
Mental contrasting of a desired future with impeding reality is a self-regulatory strategy fostering goal pursuit. However, there is little research on mental contrasting of a negative future with a positive reality. We conducted 2 experiments, each with 4 experimental conditions, investigating the effects of mental contrasting a negative future with a positive reality on state anxiety: Participants who mentally contrasted a negative future regarding a bacterial epidemic (Study 1, N = 199) or an idiosyncratic negative event (Study 2, N = 206) showed less state anxiety than participants who imagined the negative future only or who reverse contrasted; participants who mentally elaborated on the positive reality also showed less state anxiety. Our findings suggest that mental contrasting of a negative future helps people reduce disproportional anxiety regarding a negative future.